A study of human computer interaction in arcade game design - Chin, Kah Yean (2014)
This study is to find the perception of users in using game design which the game design has been applied Human Computer Interaction (HCI) rules into it. By using the HCI rules, we can enhance our game design interface, usability and functionality to increase the satisfaction of user in using the application. In order to implement the research, multimedia development life cycle (MDLC) is used to conduct the research study in order to develop a game prototype application based on the HCI framework. A review is done on the Human Computer Interaction (HCI), the Heuristic Usability Rules, HCI in games, comparing types of games and its interface design and usability and relate the human computer interaction with game design. The game design of the prototype game application is improved in terms of usability and interface design based on the specified HCI framework. Data is collected from respondents in the first stage of interview on the sample game testing. In the second stage of survey session, respondents have to test the game prototype with implemented proposed framework and again they have to give comments and also do some questionnaire regarding to the game design. Results are collected and compare with the analyzed result obtained from first interview session. Based on the result obtained, 95% of the respondents prefer the game prototype design with implemented the proposed HCI framework designed. The result is important as it can prove that the nine rules of HCI framework should be applied into the design of game design. The framework is important for game developer to have better understanding to the game design.